Syntonic phototherapy versus part time occlusion for treatment of refractive amblyopia - Sanaa Ahmed Mohamed; Adel Mohammed Abdel-Wahab Khalil; Maha Emhammed Almokhtar Aljaghmani (Scientific Reports, 2025)
Abstract To evaluate the effectiveness of syntonic phototherapy and compare it with partial time occlusion to improve visual acuity in cases of refractive amblyopia. This study is a prospective, comparative, and randomized study. It included 40 patients. Their mean age ± SD was 14.45 ± 10.03 years (Range: 6–45 years). Twenty patients were subjected to partial time occlusion of the sound eye, and 20 received syntonic phototherapy treatment.The study revealed that there was statistically significant improvement in visual functions, UCVA, BCVA, AOP, and functional visual field in patients who were subjected to syntonic phototherapy, whereas the improvement of UCVA and BCVA in patients who were subjected to conventional treatment was satisfactory but less than that reported by syntonic therapy. Visual acuity increased significantly in patients with amblyopia after syntonic phototherapy as compared to partial occlusion therapy.